cos³x - sin³x = cos 2x
0 ≤ x ≤ 3*π/2
(cos x - sin x) * (cos²x + cos x * sin x + sin²x) = (cos x - sin x) * (cos x + sin x)
1) cos x - sin x = 0
sin x = cos x
tg x = 1
x = π/4 + π * n
2) 1 + cos x * sin x = cos x + sin x
Поскольку (cos x + sin x)² = cos²x + 2 * sin x *cos x + cos²x = 1 + 2 * sin x *cos x
то sin x * cos x = ((cos x + sin x)² - 1)/2
Положив cos x + sin x = y , получаем уравнение
1 + (у² - 1) / 2 = y
2 + y² - 1 - 2 * y = 0
y² - 2 * y + 1 = 0
(y - 1)² = 0
у = 1
Получаем cos x + sin x = 1
√ 2 * cos (x - π/4) = 1
cos (x - π/4) = 1 / √ 2
x - π/4 = ± π / 4 + 2 * π * m
x = π/4 ± π / 4 + 2 * π * m
Интервалу [ 0 ; 3 * π / 2] принадлежат следующие значения х
х₁ = 0 х₂ = π/4 x₃ = π/2 x₄ = 5*π/4
3(x+20)-4x=10 2x+3(x+10)=380 5(x+2)-6(x-2)=5
3x+60-4x=10 2x+3x+30=380 5x+10-6x+12=5
3x-4x=10-60 2x+3x=380-30 5x-6x=5-10-12
-1x=-50 5x=350 -1x=-17
x=-50/-1 x=350/5 x=-17/-1
x=50 x=70 x=17
1) 5а +3b
2) - 11x+13y
3)4c^2-8c+7
4) v+u